Adolescent Gambling: Research and Clinical Implications - Wilber, Mary K. (Matrix Medical Communications, 2006)
Gambling is a popular and prevalent behavior among adolescents. As compared with adults, adolescents have been found to have high rates of problem and pathological gambling. However, relatively few adolescents seek help for gambling problems. In this article, we review adolescent gambling, including problem and pathological levels. We consider the neurobiology of adolescent gambling, health correlates of different levels of gambling participation, and manners in which current prevention and treatment strategies might be further developed and optimized.